The Influence of Audit Quality, Financial Distress, Audit Tenure, Debt Default, and Audit Delay on Going Concern Audit Opinion: A Case Study on Transportation and Logistics Service Companies Listed on the Indonesia Stock Exchange in 2018-2022 - Zelovena, Syabina Maharani; Yudi, Yudi; Rahayu, Rahayu (PT. Riset Press International, 2024)
This research aims to examine the influence of Audit Quality, Financial Distress, Audit Tenure, Debt Default and Audit Delay on Going Concern Audit Opinions simultaneously and partially. This research is quantitative research. The population in this research is the Transportation and Logistics Sector Services companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period which have been audited totaling 36 companies. The sampling method was carried out using a purposive sampling method. The sample in this study was 17 companies over 5 years, so the total sample in this study was 85. The data analysis method used to test the hypothesis was descriptive statistics and logistic regression analysis using SPSS version 26 software. The results of this study indicate that Audit Quality, Financial Distress, Audit Tenure, Debt Default and Audit Delay simultaneously influence the Going Concern Audit Opinion. Meanwhile, partially Audit Quality and Audit Delay influence the Going Concern Audit Opinion. Financial Distress, Audit tenure, and Debt Default have no effect on Going Concern Audit Opinion.